INVESTIGATION ON THE FLEXURAL STRENGTH OF PALM KERNEL SHELL CONCRETE FOR STRUCTURAL APPLICATIONS (Malaysian Journal of Civil Engineering, 2018)
An increase in the cost of conventional aggregate and the resulting environmental ecological imbalance has propelled research in the use of organic and industrial wastes as alternatives. The use of palm kernel shell concrete (PKSC) for structural applications such as beams is yet to be explored, mainly as a result of fewer research in the flexural strength of PKSC. This study investigates the flexural strength of palm kernel shell concrete (PKSC) for structural applications such as beams. Standard 150 x 150 x 150mm cube size and 100 x 100 x 500mm prisms of PKSC samples were casted at 1:1:2 mix ratio at water cement ratio of 0.5, and tested at age of 7, 14, 21 and 28 days according to BS EN 12390 – 3 (2002) and BS EN 12390 - 5 (2000). Method of batch by volume was adopted. At 28 days, the results show that the PKSC beam can support a load of 3981N with a deflection and flexural strength of 0.947mm and 2.883N/mm2 respectively. Also, the theoretical values of flexural strength and deflection compares well with the experimental values. A power equation in the form y = axn relating flexural strength with compressive strength produced a R2 value of 0.94 and relative predictive error of 0.028, the latter compares well with ACI 363 (1992) minimum value of 0.026 for power equations.